Rules of summer - Tan, Shaun (Arthur A. Levine Books, an imprint of Scholastic Inc., 2014)
Two boys explain the occasionally mysterious "rules" they learned over the summer, like never eat the last olive at a party, never ruin a perfect plan, and never give your keys to a stranger.